Exploring Vitamin D Deficiency and IGF Axis Dynamics in Colorectal Adenomas - George Ciulei; Olga Hilda Orășan; Angela Cozma; Vasile Negrean; Teodora Gabriela Alexescu; Simina Țărmure; Florin Eugen Casoinic; Roxana Liana Lucaciu; Adriana Corina Hangan; Lucia Maria Procopciuc (Biomedicines, 2024)
(1) Colorectal cancer is a major cause of cancer-related death, with colorectal adenomas (CRAs) serving as precursors. Identifying risk factors such as vitamin D deficiency and the insulin-like growth factor (IGF) axis is crucial for prevention. (2) This case–control study included 85 participants (53 CRA patients and 32 controls) who underwent colonoscopy. We measured serum vitamin D3 (cholecalciferol), calcidiol (vitamin D metabolite), calcitriol (active vitamin D metabolite), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-3 (IGFBP-3) to explore their associations with CRA risk. (3) Results: We found that lower cholecalciferol levels were a significant risk factor for CRA (OR = 4.63, p = 0.004). Although no significant differences in calcidiol and calcitriol levels were observed between CRA patients and controls, calcidiol deficiency was common in the study population. IGF-1 levels inversely correlated with age, calcitriol, and IGFBP-3 in CRA patients. (4) This study highlights the potential of lower cholecalciferol levels to detect patients at risk of CRA when calcidiol values cannot, suggesting the importance of evaluating different vitamin D metabolites in cancer prevention research. Our findings underscore the need to further investigate the interactions between calcitriol, the active form of vitamin D, and the IGF axis in colorectal cancer development.